Sistem Informasi Layanan Internship Mahasiswa Pada Sekretariat DPRD Provinsi Sumatera Selatan - M. Calvin Septiano. K; Muhamad Son Muarie (LPPM Universitas Putera Batam, 2025)
The student internship services at the Regional House of Representatives (DPRD) Secretariat of South Sumatra Province are still conducted manually, covering registration, proposal submission, logbook recording, certificate issuance, and assessment. This process often causes delays, risks of document loss, and limited transparency and data accuracy. This study aims to design and develop a web-based Student Internship Service Information System using the Rapid Application Development (RAD) method, emphasizing speed and direct user involvement at each stage. Data were collected through field observations, informal interviews, document analysis, and literature review, then processed through requirement planning with a fishbone diagram, system design using UML and ERD in the design workshop stage, and implementation with the Laravel framework. The system includes modules for registration and authentication, document uploads, daily logbook recording and printing, an admin dashboard for participant management, and digital certificate and grade generation. Black-box testing was applied to all modules, including registration, authentication, document uploads, logbook recording, participant management, and certificate and grade generation. Tests with various input scenarios verified that each function worked according to specifications. Results show that all modules functioned well, with no errors in core processes, providing accurate feedback and supporting real-time tracking of internship status. This research contributes a comprehensive internship information system model for a regional legislative environment, serving as a reference for digitalizing public services in other local government